Morphometric and morphological variants of pterion with its clinical importance in South Indian population - Mythraeyee Prasad; Sipra Rout (National Journal of Clinical Anatomy, 2022)
Background: Pterion is a critical neuroanatomical landmark in various neurosurgical approaches, including for the placement of burr holes. In addition, it also holds significance from radiological, anthropological, and forensic point of view. Thus, we undertook the current study to investigate the prevalence of different morphological types of pterion along with their morphometric parameters from adjacent bony landmarks in the south Indian population. Methodology: A total of 64 adult dry human skulls of unknown gender and age were included for the study. All skulls were grossly normal. The types of pterions were classified on both sides based on Murphy's classification. The vertical linear distance from the center of the pterion to the zygomatic arch (PZ) and to the anterior border of the frontozygomatic suture (PF) was measured with a digital vernier caliper. Data were statistically analyzed. Results: All four varieties of pterion were noticed. The sphenoparietal variety was found as most predominant bilaterally (81%), followed by epipteric (12.5%) stellate (3.9%) and frontotemporal (2.39%). One of the epipteric varieties consists of an unusually large ossicle. Pterion was typically located 3.59 ± 0.43cm behind the fronto zygomatic suture and 3.71 ± 0.34 cm above the zygomatic arch. Conclusion: The sphenoparietal variant of pterion was predominant on both sides, followed by epipteric variety.